Architect's model of Las Plazas del Mundo (Plazas of the World) (Plastichrome of Texas, Inc.)
Shown is architect's model of Las Plazas del Mundo (Plazas of the World), HemisFair's international area, where more than thirty foreign governments will have exhibits.